ANALYSIS OF SEA SURFACE HEIGHT ANOMALY CHARACTERISTICS BASED ON SATELLITE ALTIMETRY DATA (CASE STUDY: SEAS SURROUNDING JAVA ISLAND) - Sartono Marpaung; Wawan K. Harsanugraha (International Journal of Remote Sensing and Earth Sciences, 2014)
Sea surface height anomaly is a oceanographic parameter that has spatial and temporal variability.Â This paper aims to determine the characters of sea surface height anomaly in the south and north seas of Java Island.Â To find these characters, a descriptive analysis of monthly anomaly data is performed spatially, zonally and temporally.Â Based on satellite altimetry data from 1993 to 2010, the analysis shows that the average of sea surface height anomaly varies, ranging from -15 cm to 15 cm.Â Spatially and zonally, there are three patterns that can be concidered as sea surface height anomaly characteristics: anomaly is higher in coastal areas than in open seas, anomaly is lower in coastal areas than in open seas and anomaly in coastal area is almost the same as in open seas.Â The first and second patterns occur in the south and north seas of Java Island.Â The third pattern occurs simultaneously in south and north seas of Java Island.Â Characteristics of temporal anomaly have a sinusoidal pattern in south and north seas of Java Island.